2021
DOI: 10.1002/ejlt.202000380
|View full text |Cite
|
Sign up to set email alerts
|

High Metal Chelating Properties from Rapeseed Meal Proteins to Counteract Lipid Oxidation in Foods: Controlled Proteolysis and Characterization

Abstract: Rapeseed meal proteins (RP) are enzymatically hydrolyzed using three individual proteases (Alcalase, Flavourzyme, and Prolyve) and the enzymatic mechanism is studied. Rapeseed hydrolysates are produced under controlled conditions and the Prolyve hydrolysate is separated by membrane filtration. Their capacity to reduce free radicals (by transfer of hydrogen or electron) or transition metals (by electron transfer) in the absence of an oxidizable substrate, their metal chelating capacity as well as the antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Proteins/peptides were able to donate protons and neutralize free radicals to terminate the radical chain reactions [ 62 ]. Durand et al [ 63 ] reported metal chelating activity of the peptides produced from rapeseed meal proteins with Prolyve (a non-specific microbial endoproteinase with subtilisin activity). Yoshie-Stark et al [ 64 ] demonstrated that pepsin-assisted hydrolysates, obtained from rapeseed protein concentrate, had significant scavenging abilities against DPPH radical.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins/peptides were able to donate protons and neutralize free radicals to terminate the radical chain reactions [ 62 ]. Durand et al [ 63 ] reported metal chelating activity of the peptides produced from rapeseed meal proteins with Prolyve (a non-specific microbial endoproteinase with subtilisin activity). Yoshie-Stark et al [ 64 ] demonstrated that pepsin-assisted hydrolysates, obtained from rapeseed protein concentrate, had significant scavenging abilities against DPPH radical.…”
Section: Resultsmentioning
confidence: 99%
“…Isolate of total rapeseed meal proteins (RPI) was hydrolyzed with the industrial acid protease Prolyve ® , in the recently reported reaction conditions [ 23 ], i.e., at pH 3, 50 °C and E/S of 1/500, during 7 h. Figure 1 shows SEC chromatograms obtained for RPI before hydrolysis and after 7 h hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Rapeseed proteins isolate (RPI) was produced from a ground rapeseed meal provided by Olead (Pessac, France): the starting protein content in the meal was 34.4%, based on dry matter basis. Then, the extraction of total proteins was made from the meal with the same protocol described by Durand et al [ 23 ]. The purity of the obtained extract (called RPI) was analyzed by Kjeldahl method with 6.25 nitrogen-to-protein conversion factor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations